2016
DOI: 10.1016/j.micres.2016.04.016
|View full text |Cite|
|
Sign up to set email alerts
|

Evaluation of acrylamide-removing properties of two Lactobacillus strains under simulated gastrointestinal conditions using a dynamic system

Abstract: The aim of this study was to evaluate the capability of Lactobacillus reuteri NRRL 14171 and Lactobacillus casei Shirota to remove dietary acrylamide (AA) under simulated gastrointestinal conditions using a dynamic system. The effects of different AA levels or bacteria concentration on toxin removal by Lactobacillus strains were assessed. Thereafter, AA-removing capability of bacteria strains under either fasting or postprandial simulated gastrointestinal conditions was evaluated. Commercial potato chips were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 47 publications
0
21
0
Order By: Relevance
“…The acrylamide concentration used in that part of the study was much higher than that detected in food. The concentrations of acrylamide reported in the literature vary from <10 to even 80,920 µg/kg, with the highest levels in potato chips, French fries, roasted coffee, and coffee extract [44,[47][48][49][50]. Considering the quantities of particular foodstuffs we consume each day, it has been estimated that total AA uptake varies from 0.3 to 1.4 µg per kg body weight per day [48], depending on the age group (high consumption of coffee in adults) and eating habits.…”
Section: Impact Of Acrylamide On Lab Growth On Solid Mediummentioning
confidence: 99%
See 1 more Smart Citation
“…The acrylamide concentration used in that part of the study was much higher than that detected in food. The concentrations of acrylamide reported in the literature vary from <10 to even 80,920 µg/kg, with the highest levels in potato chips, French fries, roasted coffee, and coffee extract [44,[47][48][49][50]. Considering the quantities of particular foodstuffs we consume each day, it has been estimated that total AA uptake varies from 0.3 to 1.4 µg per kg body weight per day [48], depending on the age group (high consumption of coffee in adults) and eating habits.…”
Section: Impact Of Acrylamide On Lab Growth On Solid Mediummentioning
confidence: 99%
“…Other studies [42,43] have shown that Lactobacillus reuteri NRRL 14171 and Lactobacillus casei Shirota are able to remove acrylamide in aqueous solution by physically binding the toxin to the bacterial cell wall, probably with a significant role of the teichoic acid structure. Later, Rivas-Jimenez [44] demonstrated that both mentioned bacterial strains were able to remove dietary AA (commercial potato chips with an average AA content of~34,000 µg/kg) under different simulated gastrointestinal conditions. The percentage of AA removed by each bacterium exposed to different concentrations of the toxin (10-350 µg/mL) had a similar tendency; the lower the concentration of AA, the higher the percentage of toxin removed.…”
Section: Introductionmentioning
confidence: 99%
“…Other toxic substances can be handled by LAB. Acrylamide-binding ability by LAB was found to be both concentration- and strain-dependent, in vitro ( Serrano-Nino et al, 2014 ) as well as in a gastric digestion stimulator ( Rivas-Jimenez et al, 2016 ); the binding was mostly based on teichoic acid properties of specific strains. These results are promising for further actions and research to reduce exposure and bioavailability of such carcinogenic compounds.…”
Section: Regardless Of Their Origin Lab Can Exhibit Multifaceted Funmentioning
confidence: 99%
“…In several studies, probiotic yeast S. boulardii was effective against C. difficile when given along with antibiotics [42]. In a number of cases, probiotic microbes such as LAB, S. boulardii, Clostridium butyricum prevented such diarrhea, although not all studies have shown probiotics to be effective [42][43][44][45].…”
Section: Effect Of Probiotics On Diarrheamentioning
confidence: 99%